Batch fertility and larval parameters of the jaguar cichlid (Cichlasoma managuense) spawned in the laboratory - Günther Nonell, Jorge (1994)
Abstract: Batch fertility and larval parameters of 32 spawns of the jaguar guapote (Cichlasoma managuense) in the laboratory were analyzed. Batch fertility was positively correlated with the female weight with spawns between about 3000 to 6000 larvae for females between 100 and 500 g wet weight. No significant correlation was found between larval parameters (fresh weight and % dry weight) and female weight.